Unraveling genomic regions with transmission ratio distortion harboring putative lethal alleles and their biological implications in Nellore cattle from experimental selection lines - Rodrigues, Gustavo R D [UNESP]; Brito, Luiz F; Mota, Lucio F M [UNESP]; Cyrillo, Joslaine N S G; Neto, João B Silva [UNESP]; Campos, Milena A F; Faro, Lenira El [UNESP]; Albuquerque, Lucia G [UNESP]; Mercadante, Maria E Z [UNESP] (Oxford University Press (OUP), 2025)
Transmission Ratio Distortion (TRD) refers to deviations from expected Mendelian inheritance patterns when alleles from heterozygous parents are transmitted at frequencies different from the expected 50%, influenced by biological mechanisms affecting reproduction. Therefore, this study aimed to 1) characterize genomic regions exhibiting TRD patterns in Nellore cattle (Bos taurus indicus), 2) detect TRD regions potentially harboring semilethal or lethal alleles, and 3) identify candidate genes and perform functional genomic enrichment analyses to reveal quantitative trait loci (QTL), biological processes, and metabolic pathways associated with TRD regions. TRD analyses were performed on a genomic dataset of 3,351 animals with 612,154 autosomal single nucleotide polymorphism (SNP) markers aligned to the ARS-UCD1.2 Bos taurus genome assembly. The software TRDscan v.2.0 was used to evaluate allelic (overall and parent-specific) and genotypic (additive and dominance) parametrizations of TRD effects using a Bayesian framework. Gene annotation, QTL identification, and functional genomic enrichment were conducted based on the locations of the identified TRD regions. A total of 37,783 SNPs and 174,190 haplotypes exhibiting TRD were identified, corresponding to 1,249 genomic regions distributed across all Bos taurus autosomes (802 overall TRD, 191 parent-specific TRD, and 256 genotypic TRD). Among these, 73 allelic TRD regions and 59 genotypic TRD regions were identified as potentially harboring semilethal or lethal alleles, with the highest number of underrepresented offspring reaching 1,501 individuals. We identified 2,265 candidate genes based on gene annotation, while functional enrichment analyses enabled the identification of 200 significant Gene Ontology (GO) terms, and 2 pathways involved in embryo development, morphogenesis, and growth regulation (P-value < 0.05). Additionally, significant enrichment of QTL associated with production and reproduction traits was observed within these TRD regions (P-value < 0.05). These findings underscore the critical importance of integrating TRD information into genomic selection strategies to enhance productive efficiency while mitigating the spread of deleterious alleles that adversely affect reproduction and embryo survival in Nellore cattle.